1991
DOI: 10.1099/00221287-137-11-2561
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the expression of cell envelope proteins of coagulase-negative staphylococci cultured under iron-restricted conditions in human peritoneal dialysate

Abstract: Strains of coagulase-negative staphylococci (CNS), including Staphylococcus epidermids, S. hominis, S. warnerii, S. simulans, S. capitis, S. haemolyticus and S. saprophyticus, were isolated from patients with continuousambulatory-peritoneal-dialysis-related peritonitis. The cell wall and cytoplasmic membrane protein profiles of CNS strains cultured in either nutrient broth (NB) or pooled human peritoneal dialysate (HPD) were compared. Some interspecies variation in both the wall and membrane protein profiles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 33 publications
4
35
1
Order By: Relevance
“…B. subtilis also has three Fur homologues, involved in the regulation of iron (Fur) (4), peroxide stress response (PerR) (4), and zinc uptake (Zur) (10). It is possible that, in addition to Fur, staphylococci have another ferric-iron repressor, SirR (15), which is a homologue of the ferric-iron repressor DtxR (32).Our previous studies identified a number of iron-regulated S. aureus and S. epidermidis proteins, which are expressed in vivo both during human infection (30,35) and in an experimental animal model (23,25). To date, only two of these proteins have been characterized.…”
mentioning
confidence: 99%
“…B. subtilis also has three Fur homologues, involved in the regulation of iron (Fur) (4), peroxide stress response (PerR) (4), and zinc uptake (Zur) (10). It is possible that, in addition to Fur, staphylococci have another ferric-iron repressor, SirR (15), which is a homologue of the ferric-iron repressor DtxR (32).Our previous studies identified a number of iron-regulated S. aureus and S. epidermidis proteins, which are expressed in vivo both during human infection (30,35) and in an experimental animal model (23,25). To date, only two of these proteins have been characterized.…”
mentioning
confidence: 99%
“…The expression of ironrepressible OMPs by coagulase-negative staphylococci grown in vitro in pooled human peritoneal dialysate closely resembled that observed in bacteria recovered from peritoneal chamber implants in an animal model [20][21][22]. Also, parent and mutant staphylococcal strains, which were found to differ markedly in their abilities to accumulate on surfaces when examined in vitro in conventional complex growth media, were indistinguishable in repeat experiments using pooled human serum.…”
Section: Discussionmentioning
confidence: 54%
“…The whole cell protein profiles of PIF grown bacteria indicated grossly reduced expression of proteins compared with broth cultured cells. Such protein repression has been noted after bacterial culture in other human body fluids and is believed to reflect nutrient limitation [20,21,24]. Several novel proteins were expressed in bacteria cultured in PIF; for example, protein bands of 24 kDa and 36 kDa were seen in the OMP profiles ofA.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Most bacteria respond to the environmental cue of restricted iron availability by derepressing siderophone-mediated iron transport systems (11). Previously, other researchers (4,5,12,13) have shown that growth of staphylococci in HPD resulted in the induction of two immunodominant, iron-regulated cytoplasmic membrane proteins. These iron-regulated proteins were thought to be putative siderophore receptors and also expressed by S. epidermidis grown in vitro in iron-restricted nutrient broth, and in vivo in a chamber implanted intraperitoneally in rats.…”
Section: Discussionmentioning
confidence: 99%